Harmonic mappings related to Janowski convex functions of complex order b - Aydoğan, Seher Melike; Kahramaner, Yasemin; POLATOĞLU, YAŞAR (My University, 2013)
Let SH be the class of all sense-preserving harmonic mappings in the open unit disc D = {z ∈ ℂ

z| < 1}. In the present paper the authors investigate the properties of the class of harmonic mappings which is based on the generalized of R. J. Libera Theorem [7].